Systema Cosmicum - Galilei, Galileo, 1564-1642 ([Netherlands] : Elsevier, 2014)
Galileo Galilei's (1564-1642) Dialogue Concerning the Two Chief World Systems was first published in Italian in 1632 (Florence). Because Galileo's comparison between the Copernican and the traditional Ptolemaic systems had caused outrage among the Catholic clergy, the book was placed on the Index of Forbidden Books. Fortunately, the manuscript was adopted by scholars throughout Europe. The Elzeviers' Latin edition, titled Dialogus Systema Mundi was published in 1635, and contains a beautiful title page, as well as a portrait of the author.
'First published by Abraham and Bonaventura Elzevier, and David Hauttus in 1635. Republished by Elsevier B.V. in 2014.'
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed March 30, 2015).
Elsevier
Keywords: Astronomy -- Early works to 1800.; Astronomy; Electronic books; Early works